Adult Education in Correctional Settings: A Critical Literature Review - Sannon Frey (Adult Education Research Conference, 2014)
This paper reviews literature relating to correctional education in five adult education journals and examines trends in adult education revealed through the analysis. Through exploration of these trends, adult educators can begin to address the motivation for offering these types of education and who it is intended to benefit.